Age of first alcohol intoxication and psychiatric disorders in young adulthood – A prospective birth cohort study. (July 2021) - Mustonen, Antti; Alakokkare, Anni-Emilia; Salom, Caroline; Hurtig, Tuula; Levola, Jonna; Scott, James G.; Miettunen, Jouko; Niemelä, Solja
Highlights: Association of age of first alcohol intoxication (AFI) and psychiatric disorders was studied. AFI≤14 was associated with later SUD; AFI≤12 with later "any psychiatric disorder". Earlier AFI was associated with an increasing risk of SUD. Abstract: Objective: Early onset of alcohol use is associated with an increased risk of substance use disorders (SUD), but few studies have examined associations with other psychiatric disorders. Our aim was to study the association between the age of first alcohol intoxication (AFI) and the risk of psychiatric disorders in a Finnish general population sample. Methods: We utilized a prospective, general population-based study, the Northern Finland Birth Cohort 1986. In all, 6, 290 15–16-year old adolescents answered questions on AFI and were followed up until the age of 33 years for psychiatric disorders (any psychiatric disorder, psychosis, SUD, mood disorders and anxiety disorders) by using nationwide register linkage data. Cox-regression analysis with Hazard Ratios (HR, with 95% confidence intervals (CI)) was used to assess the risk of psychiatric disorders associated with AFI. Results: Statistically significant associations were observed between AFI and any psychiatric disorder, psychosis, SUDs, and mood disorders. After adjustments for other substance use, family structure, sex and parental psychiatric disorders, AFIs of 13–14 years and ≤12 years were associated with SUD (HR = 5.30; 95%CI 2.38–11.82 and HR = 6.49; 95%CI 2.51–16.80, respectively), while AFI ≤ 12 years was associated with any psychiatric disorder (HR = 1.59; 95%CI 1.26–2.02) and mood disorders (HR = 1.81; 95%CI 1.22–2.68). After further adjustments for Youth Self Report total scores, AFI ≤ 14 was associated with an increased risk of SUD and AFI ≤ 12 with an increased risk of any psychiatric disorder. Conclusions: We found significant associations between the early age of first alcohol intoxication, later SUD and any psychiatric disorder in a general population sample. This further supports the need for preventive efforts to postpone the first instances of adolescent alcohol intoxication.